Implementation of Nature-Based Learning in Forming Environmentally Loving Character of Students at Fadilatul As'adiyah Teluno Elementary School - Rustan Deki Rustan; Nurhayati Nurhayati; M. Askari Zakariah (JISIP: Jurnal Ilmu Sosial dan Pendidikan, 2026)
This study aims to analyze the implementation of nature-based learning in shaping students' environmental character at Madrasah Ibtidaiyah Fadilatul As'adiyah Teluno. This study uses a qualitative approach with a case study design to examine in depth the planning, implementation, and evaluation processes of nature-based learning and its impact on student character formation. Data were collected through semi-structured interviews, direct observation, and documentation involving the principal, fifth-grade teachers, and students. Data analysis was carried out through the stages of data reduction, data presentation, and concluding using thematic analysis techniques, while data validity was maintained through triangulation of sources and methods. The results of the study indicate that nature-based learning is implemented systematically through integrated planning in learning tools, implementation of experiential learning activities directly in the school environment, and ongoing character evaluation. This implementation has a positive impact on the formation of environmental character as demonstrated by increased awareness, responsibility, initiative, and collective commitment of students in maintaining the cleanliness and sustainability of the school environment. Thus, nature-based learning can be an effective pedagogical strategy in integrating cognitive understanding and character building sustainably at the elementary education level.